Phase noise suppression in Microstructured Fibers - Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (International Quantum Electronics Conference 2004, 2004)
We investigated thermal phase-noise in a microstructured fiber. We demonstrate that the microstructure of the fiber establishes a low order acoustic resonator thus suppressing all guided acoustic wave Brillouin scattering modes up to 300 MHz.<br